Health Information Exchange Organizations and Their Support for Research: Current State and Future Outlook. (12th June 2017) - Parker, Carol; Reeves, Mathew; Weiner, Michael; Adler-Milstein, Julia
Federal investment spurred health information exchange organization (HIO) development and maturation to provide third-party approaches to electronic health information exchange across disparate electronic health record (EHR) systems. By creating opportunities for data aggregation across multiple medical institutions, HIOs also spur research. Using data from a 2015 national web-based survey of HIOs (N = 64), we identified HIOs supporting or not supporting research, and compared characteristics of the 2 groups. We found that 15 (23%) of the 64 HIOs reported supporting research, 30 (47%) reported planning to support research, and 19 (30%) did not support research. Research-supporting HIOs were more likely than nonresearch supporting HIOs to offer advanced functionality, such as allowing users to query and retrieve data from multiple sources. Our study offers encouraging preliminary evidence that HIOs are supporting research, which could offer a solution to current challenges in creating comprehensive longitudinal clinical data sources for research.